2013
DOI: 10.1111/sms.12047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training cessation on muscular performance: A meta‐analysis

Abstract: The purpose of this study was to assess the effect of resistance training cessation on strength performance through a meta-analysis. Seven databases were searched from which 103 of 284 potential studies met inclusion criteria. Training status, sex, age, and the duration of training cessation were used as moderators. Standardized mean difference (SMD) in muscular performance was calculated and weighted by the inverse of variance to calculate an overall effect and its 95% confidence interval (CI). Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
3
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 67 publications
7
90
3
10
Order By: Relevance
“…Results indicate that (i) five weeks only of off-season detraining in the CG induced a deterioration of speed/power and endurance performance which was more pronounced in eccentric strength of KF and concentric strength of KE; (ii) a five-week periodized complex training program not only attenuated the decline of 23 Since no changes were observed in body composition, a plausible explanation for these reductions of muscle strength is probably a compromised neural input. Detraining effects on performance are related to factors such as maturation, training level, and total training load before training cessation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Results indicate that (i) five weeks only of off-season detraining in the CG induced a deterioration of speed/power and endurance performance which was more pronounced in eccentric strength of KF and concentric strength of KE; (ii) a five-week periodized complex training program not only attenuated the decline of 23 Since no changes were observed in body composition, a plausible explanation for these reductions of muscle strength is probably a compromised neural input. Detraining effects on performance are related to factors such as maturation, training level, and total training load before training cessation.…”
Section: Discussionmentioning
confidence: 89%
“…1RM increased by 21-30%, a magnitude of improvement that has been previously reported for youth 26 and may be related to participants' minimal previous involvement with ST. 26 These gains cannot be attributed to an upregulation fat-free mass since body composition remained unchanged suggesting that neural factors have probably contributed to these adaptations within such a short time frame. 23 Furthermore, isokinetic testing revealed that the ratios of peak torques of KF and KE remained unchanged or slightly increased but remained within their physiological range indicating a reduced risk for hamstrings' injury. 20 Speed improvement (~4%) was of similar magnitude with that usually reported for youth exposed to ST. 27 However, others failed to observe changes in speed despite a rise in muscle power in response to ST. 26 This discrepancy among studies is probably related to differences in the type of exercises used, planes of movements and muscles recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, training interruption may lead to detraining, which can result in loss of important adaptations, such as reductions of muscle mass, bone mineral density and content, strength, power, muscular endurance, balance, and coordination (Bosquet et al 2013;Correa et al 2013;Lovell et al 2010). Giving this information, we cannot rule out the possibility that OS biomarkers may also be affected by detraining.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos Polimento e Basquetebol | 9 têm demonstrado que a resistência anaeróbia de atletas pode aumentar logo no início da temporada competitiva (Bosquet et al, 2013;Ramírez-Campillo et al, 2016). Este fato pode ser explicado em razão da redução do desempenho físico após o período transitório entre duas temporadas competitivas, também conhecido como efeito destreinamento (Bosquet et al, 2013).…”
Section: Discussionunclassified
“…Estudos Polimento e Basquetebol | 9 têm demonstrado que a resistência anaeróbia de atletas pode aumentar logo no início da temporada competitiva (Bosquet et al, 2013;Ramírez-Campillo et al, 2016). Este fato pode ser explicado em razão da redução do desempenho físico após o período transitório entre duas temporadas competitivas, também conhecido como efeito destreinamento (Bosquet et al, 2013). Por conseguinte, os atletas retornam a sua rotina de treinamento, o que acarreta aumento progressivo de habilidades motoras (Loturco et al, 2015), por exemplo a resistência anaeróbia, o que, de certo modo, pode explicar o aumento desta variável ao final do período preparatório no presente estudo.…”
Section: Discussionunclassified